First Detection of Two Near‐Earth Asteroids With a Southern Hemisphere Planetary Radar System. Issue 11 (9th November 2017) - Benson, Craig; Reynolds, John; Stacy, N. J. S.; Benner, Lance A. M.; Edwards, P. G.; Baines, Graham; Boyce, Russell; Giorgini, Jon D.; Jao, Joseph S.; Martinez, George; Slade, Martin A.; Teitelbaum, Lawrence P.; et al.
Abstract: We describe the first demonstration of a Southern Hemisphere planetary radar system to detect two near‐Earth asteroids (NEAs). The demonstration was conducted in a bistatic manner, with the 70 m antenna of the Canberra Deep Space Communications Complex transmitting at 2.1 GHz and reception at the Parkes Radio Telescope, outfitted with multiple receivers, and the Australia Telescope Compact Array. This initial system was used to detect the NEAs (43577) 2005 UL5 and (33342) 1998 WT24 during their close approaches in 2015 November and 2015 December, respectively. We describe the performance of the system and consider future possibilities using other antennas of the Canberra Deep Space Communications Complex as transmitters. Plain Language Summary: Planetary radar uses large radio dishes to transmit and receive radar signals off distant objects in the solar system. Careful processing of these signals over periods of several hours allows researchers to very accurately determine orbits, measure rotation rates, and in some cases to map surface features. In the past all of these activities have been performed with assets in the Northern Hemisphere. This paper details the first use of a Southern Hemisphere network for this task. The 70 m dish at the NASA/JPL/CSIRO complex at Tidbinbilla in Canberra, Australia, was used as the transmitter, and the Parkes and Narrabri radio telescopes were used as receivers to successfully detect and track asteroids. A Southern Hemisphere network allows asteroids approaching from the south to be observed, filling in a blind spot in our existing capabilities. Key Points: This is the first detection of a Southern Hemisphere planetary radar system Future Southern Hemisphere radar observations will augment existing Northern Hemisphere capabilities